2004
DOI: 10.7326/0003-4819-141-7-200410050-00011
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review: Computed Tomography and Ultrasonography To Detect Acute Appendicitis in Adults and Adolescents

Abstract: Computed tomography is probably more accurate than ultrasonography for diagnosing appendicitis in adults and adolescents. Prospective studies that apply gold standard diagnostic testing to all study participants would more reliably estimate the true diagnostic accuracy of these tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
221
4
10

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 359 publications
(249 citation statements)
references
References 108 publications
14
221
4
10
Order By: Relevance
“…This is while the diagnostic accuracy of radiologist performed ultrasound study in diagnosis of acute appendicitis still remains conflicting and indistinct, and different studies show different results. As Terasawa et al showed in their review on 14 studies that ultrasonography has a sensitivity of 86 %, specificity of 81 %, positive predictive value of 84 % and a negative predictive value of 85 % in diagnosing acute appendicitis in patients with right lower quadrant pain and suspicious to have acute appendicitis [7], a large meta-analysis (including 22 articles) in Korea found also a sensitivity of 87 % and specificity of 90 % for sonography in acute appendicitis and another review by Pinto et al showed also the acceptable overall accuracy for ultrasound study in diagnosis of acute appendicitis [8]. But there are other studies showing positive predictive value ranging from 46 to 95 % and the negative predictive value ranging from 60 to 97 % for this diagnostic imaging modality [9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…This is while the diagnostic accuracy of radiologist performed ultrasound study in diagnosis of acute appendicitis still remains conflicting and indistinct, and different studies show different results. As Terasawa et al showed in their review on 14 studies that ultrasonography has a sensitivity of 86 %, specificity of 81 %, positive predictive value of 84 % and a negative predictive value of 85 % in diagnosing acute appendicitis in patients with right lower quadrant pain and suspicious to have acute appendicitis [7], a large meta-analysis (including 22 articles) in Korea found also a sensitivity of 87 % and specificity of 90 % for sonography in acute appendicitis and another review by Pinto et al showed also the acceptable overall accuracy for ultrasound study in diagnosis of acute appendicitis [8]. But there are other studies showing positive predictive value ranging from 46 to 95 % and the negative predictive value ranging from 60 to 97 % for this diagnostic imaging modality [9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonography had an overall sensitivity of 86%, a specificity of 81%. 7 In 2006, a meta-analysis by Doria et al demonstrated that CT imaging featured significantly higher sensitivity and resolution than ultrasound in studies of both children and adults with acute appendicitis. 8 The use of CT for diagnosis of appendicitis in Boston, MA has decreased the chance of finding a normal appendix at surgery from 20% in the pre-CT era to only 3% according to data from the Massachusetts General Hospital.…”
Section: Discussionmentioning
confidence: 99%
“…In his original paper [11] Alvarado recommended an operation for all patients with a scores of 7 or more and observation for patients with scores of 5 or 6. Similarly imaging studies such as ultrasound have an average sensitivity and specificity of around 85-90% [13,14]. Thus incorporating repeated clinical examination, using diagnostic scoring systems and use of imaging has resulted in better diagnostic outcome [15].…”
Section: Discussionmentioning
confidence: 99%